Cyberbullying di Media Sosial dalam Perspektif Al-Quran: Studi Terhadap Qs Al-Hujurat Ayat 11 - Iman, Imanuddin; Mursalim, Mursalim (Indo-MathEdu Intellectuals Journal, 2024)
The phenomenon of Cyberbullying in the digital era challenges global society with aggressive behavior aimed at causing emotional harm through digital media. The Koran provides holistic guidance in dealing with this problem, especially Surah Al-Hujurat verse 11 which prohibits insulting and criticizing behavior. The research aims to analyze the concept of cyberbullying on social media according to the views of the Al-Qur'an surah Al-Hujurat verse 11 and identify its impact. This research uses qualitative methods with a literature study approach to understand more deeply this phenomenon from a religious perspective. The data sources for this research come from literature and library sources related to the phenomenon of cyberbullying according to the Al-Qur'an, including texts, articles, journals and other scientific literature. Data collection was carried out through various relevant sources, then analysis was carried out using the content analysis method to identify important characteristics and information related to this research. The results show that the values in Surah Al-Hujurat verse 11 such as politeness, respect and behavior towards others are very relevant in overcoming the Cyberbullying phenomenon that occurs with the development of time and technology. Practical implications include education, training, and social campaigns to create safer and more inclusive online environments